Separate teaching and separate transmission: Kokan Shiren's Zen polemics - Licha, Stephan (Japanese journal of religious studies, 2018)
This article investigates the thought of Kokan Shiren (1278-1346), a representative of the Five Mountains Zen institution. It argues that Kokan's understanding of Zen developed in the context of a polemic against and consequently under the influence of the classical schools of Japanese Buddhism, especially Tendai. It focuses on Kokan's interpretation of Zen's claim to represent a "separate transmission outside the teachings," his exposition of the La?kāvatāra Sūtra, and finally his initiatory characterization of the Zen lineage, and shows that Kokan developed an exclusivistic vision of Zen that significantly differs from the universalist tendencies of his predecessors such as Eisai (1141-1215) or Enni (1202-1280). The article concludes that the development of early medieval Zen ideology needs to be positioned in the context of contemporary Japanese Buddhist doctrinal debates and cannot be seen as a simple continuation of Chinese precedents.
Keywords: Geschichte 1100-1400; Klassifikation; Tiantai-Schule; Polemik; Zen-Buddhismus; Lankāvatāra-sūtra; Kokan